2017
DOI: 10.3390/nu9090920
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Amino Acids in Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD), which includes both ulcerative colitis and Crohn’s disease, is a chronic relapsing inflammation of the gastrointestinal tract, and is difficult to treat. The pathophysiology of IBD is multifactorial and not completely understood, but genetic components, dysregulated immune responses, oxidative stress, and inflammatory mediators are known to be involved. Animal models of IBD can be chemically induced, and are used to study etiology and to evaluate potential treatments of IBD. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
97
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(104 citation statements)
references
References 127 publications
(187 reference statements)
5
97
2
Order By: Relevance
“…Our results suggested that productions of IL‐6, IL‐12, and TNF‐α were significantly reduced by TEs, whereas productions of IL‐10 were significantly increased by TEs compared to that of DSS group. These findings were similar to the previous studies, which indicated the therapeutic effects of phytochemicals enriched extracts from tea, fruits, as well as the individual phytochemicals involving epigallocatechin gallate, rutin, and free amino acids in colitis mice …”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Our results suggested that productions of IL‐6, IL‐12, and TNF‐α were significantly reduced by TEs, whereas productions of IL‐10 were significantly increased by TEs compared to that of DSS group. These findings were similar to the previous studies, which indicated the therapeutic effects of phytochemicals enriched extracts from tea, fruits, as well as the individual phytochemicals involving epigallocatechin gallate, rutin, and free amino acids in colitis mice …”
Section: Resultsmentioning
confidence: 96%
“…Flavonoids and phenolic acids‐enriched fruits, such as Muntingia calabura Linn , Citrus sinensis (sweet orange), Vitis rotundifolia (muscadine grape), suppressed the activation of NF‐κB in LPS‐stimulated cell models or DSS‐induced colitis models . Meanwhile, the phytochemicals in TEs, such as catechins and amino acids, are known to alleviate anti‐inflammatory effects by inhibiting the activation of NF‐κB in colitis mice model . Thus, in the present study, the bioactive phytochemicals in TEs might singly or synergistically inactive NF‐κB to exhibit the anti‐inflammatory effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a role for amino acids in gastrointestinal (GI) health. Amino acids such as arginine, glutamine, glycine, cysteine, N ‐acetylcysteine, and proline have functions in the GI tract such as attenuation of gut damage, support of intestinal barrier function and integrity, reduction in oxidative stress, restoration of mucosal immune homeostasis, and optimization of function by normalizing or reducing inflammatory cytokine secretion and increasing immune regulatory cytokine concentrations . Recent studies have increasingly focused on the role of amino acids in the pathogenesis and treatment of humans with inflammatory bowel disease (IBD) and animal models of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…combination therapy with intraperitoneal injection of ASCs and sulfasalazine in a rat model of TNBS-induced colitis. TNBS-induced colitis in rat is characterized by transmural intestinal inflammation and dysregulation of innate and adaptive immune responses that present characteristics similar to those of human IBD(Liu, Wang, & Hu, 2017).MSCs are a heterogeneous subset of stromal cells with selfrenewal ability and multipotent differentiation potential that canbe isolated from fat, bone marrow, umbilical cord, amniotic fluid, placenta, and other tissues. MSCs have been demonstrated to exert potent anti-inflammatory and immunomodulating effects on almost all the cells of the innate and adaptive immune systems via direct cell-cell contact and secretion of soluble paracrine factors, such as cytokines and chemokines (Kyurkchiev et al, 2014).…”
mentioning
confidence: 99%